(untitled) (Journal of Universal Science Research, 2023)
It is certainly vital for communicating in any languages, humans are in need of all parts of speech, though one of the most indispensable parts is noun. Nouns are the most numerous class of words (42% of all words). This article is devoted to give information about English noun and grammatical categories such as number, case, gender as well as give examples illustrating the topic in detail providing different graphs.